PENGARUH KOMPENSASI, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION PADA PT. PINUS MERAH ABADI CABANG DENPASAR - I Made Agus Mertha Dana; I Ketut Sutapa (Universitas Triatma Mulya, 2023)
This study aims to determine the effect of compensation, workload and workenvironment on employee turnover intention at PT. Pinus Merah Abadi DenpasarBranch. Based on the results of data analysis, the regression equation was found: Y =35.199 – 0.410X1 + 0.355X2 – 0.213X3. The results of the analysis of thecompensation variable show tcount -3.528 > ttable -1.99773 with a significance levelof 0.001 <0.05, meaning that compensation (X1) has a negative and partiallysignificant effect on employee turnover intention (Y) at Pinus Merah Abadi DenpasarBranch. For the results of the analysis of the workload variable, it shows a tcount of3.322 > a ttable of 1.99773, and a significant value of 0.001 <0.05, meaning thatworkload (X2) has a positive and partially significant effect on employee turnoverintention (Y) at Pinus Merah Abadi Denpasar Branch. The results of the analysis ofwork environment variables show a tcount of -2.140 > ttable of -1.99773, and asignificant value of 0.036 <0.05, meaning that the work environment (X3) has anegative and partially significant effect on employee turnover intention (Y) at PinusMerah Abadi Denpasar Branch. Based on the results of the fcount test of 13.316 >ftable of 2.75 and the Sig. of 0.000 <0.05 so that it can be concluded that the variablecompensation (X1), workload (X2) and work environment (X3) have a simultaneouspositive and significant effect on employee turnover intention (Y) at Pinus MerahAbadi Denpasar Branch. Based on the results of the coefficient of determination it wasfound that the influence contributed by the variable compensation (X1), workload (X2)and work environment (X3) on employee turnover intention (Y) at Pinus Merah AbadiDenpasar Branch is 38.4% and the remaining 61.6% is influenced by other variablesnot examined in this study. The results of this study also show that the compensationvariable (X1) has the most dominant influence on employee turnover intention (Y) atPinus Merah Abadi Denpasar Branch is -0.385